Lecithin-coated gold nanoflowers (GNFs) for CT scan imaging applications and biochemical parameters; in vitro and in vivo studies. (31st October 2018) - Aziz, Farooq; Bano, Khizra; Siddique, Ahmad Hassan; Bajwa, Sadia Zafar; Nazir, Aalia; Munawar, Anam; Shaheen, Ayesha; Saeed, Madiha; Afzal, Muhammad; Iqbal, M. Zubair; Wu, Aiguo; Khan, Waheed S.
Abstract: We report a novel strategy for the fabrication of lecithin-coated gold nanoflowers (GNFs) via single-step design for CT imaging application. Field-emission electron microscope confirmed flowers like morphology of the as-synthesized nanostructures. Furthermore, these show absorption peak in near-infrared (NIR) region at λmax 690 nm Different concentrations of GNFs are tested as a contrast agent in CT scans at tube voltage 135 kV and tube current 350 mA. These results are compared with same amount of iodine at same CT scan parameters. The results of in vitro CT scan study show that GNFs have good contrast enhancement properties, whereas in vivo study of rabbits CT scan shows that GNFs enhance the CT image clearly at 135 kV as compared to that of iodine. Cytotoxicity was studied and blood profile show minor increase of white blood cells and haemoglobin, whereas decrease of red blood cells and platelets.